Assessing the impact of e-entrepreneurship orientation key success factors on banks’ performance - Laghouag, Abderrazak Ahmed (Management and Entrepreneurship: Trends of Development, 2022)
The 2030 Vision for Saudi Arabia emphasizes an increase in SMEs' contributions to the national economy from 20% to 35%, and a reduction in unemployment from 11.6% to 7%. This requires banks to play a crucial role in supporting entrepreneurial projects, which the Kingdom relies upon. Saudi Arabia's banks took advantage of this opportunity to gain more customers and market share by being more innovative and proactive, and willing to take risks concerning e-services. The purpose of this study includes evaluating banks' performance in KSA considering entrepreneurship orientation drivers in E-banking. The methodology: For testing these hypotheses, a questionnaire has been created and filled out by banks’ workers. The findings: Actually, E-banking entrepreneurial orientation is strongly supported by human capital as evidenced by the research results. On the other hand, the results show a significant positive impact of e-banking entrepreneurial orientation on three dimensions of bank performance, namely, competitiveness, financial performance, and customer services.JEL Classification: L25, L26, G20